PERLINDUNGAN ANAK DI BAWAH UMUR TERHADAP PENYALAHGUNAAN NARKOBA DI KAWASAN PERBATASAN - Fernando, Yudha Febry (Universitas Borneo Tarakan, 2023)
AbstractChildren are the successors of the nation whose rights must be fulfilled, such asthe right to life and development. Childhood is a period that is very vulnerablewith various desires and hopes to achieve something or do something, includingnegative things which ultimately lead to the wrong path (for example usingdrugs). Especially in the border area (North Kalimantan), which can be said tobe the